Influencia de la depresión en la adherencia al tratamiento antirretroviral en pacientes con VIH/SIDA del Hospital Regional de Loreto - 2022 - Trigoso Pacaya, Cinthya Estefita (2023)
Objectives: To evaluate the influence of depression on adherence to antiretroviral treatment (ART) in patients at the Regional Hospital of Loreto, Peru (HRL) during 2022. Methods: Observational cross-sectional study with 261 patients with HIV. The PHQ-9 was used to measure depression and the CEAT-HIV to assess adherence to ART. Results: 29.5% (n=77) of patients present strict adherence to treatment, statistically significant associations were found between non-adherence to ART and sociodemographic, clinical and depression characteristics. A 3.3 times higher risk of non-compliance was observed in patients between 19 and 45 years of age; 3.2 times higher risk in heterosexuals; 10.2 times higher risk in rural areas and singles had 2.3 times higher risk than married or cohabiting. Patients with 5 to 10 years of diagnosis were 3.5 times more likely to be nonadherent compared to those 10 years or older; 6.6-fold higher odds of nonadherence with moderate viral load, and alcohol use prior to diagnosis was associated with a 3.3-fold higher odds of treatment nonadherence compared with never-drinkers. Finally, patients with depression had a 24 times greater risk of not adhering to treatment compared to those without depression. Conclusions: This study confirmed that some level of depression is strongly related to non-adherence to ART in HIV HRL patients in 2022.